CINTA KASIH DAN ETIKA DALAM PERSPEKTIF TINDAKAN SOSIAL TALCOTT PARSONS DALAM NOVEL GURU AINI KARYA ANDREA HIRATA (LOVE AND ETHICS IN THE PERSPECTIVE OF TALCOTT PARSONS' SOCIAL ACTION IN ANDREA HIRATA'S NOVEL GURU AINI) - Ariskadyani Meiferawati (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA, 2023)
AbstractLove and Ethics in the Perspective of Talcott Parsons' Social Action in Andrea Hirata's Novel Guru Aini. This study aims to describe the representation of love and ethics in the social action perspective of Talcott Parsons and the representation of love and ethics in reconstructing the world of education in Andrea Hirata's Novel Guru Aini. The method used in this research is the sociology of literature. In this study, literature is treated as a social document. The data source in this study was the text of Andrea Hirata's Novel Guru Aini. Data were collected using literature study techniques. The study's results showed 77 social actions in the aspects of love and ethics based on the social action perspective of Talcott Parsons. The representation of love includes love for parents, fellow human beings, and work. The picture of love in Talcott Parsons' social action perspective shows four social actions: the cultural system, the social system, the personality system, and the organism system. Ethical representation includes ethics toward parents, fellow human beings, and society. The picture of ethics in Talcott Parsons' social action perspective shows four social actions: the cultural system, the social system, the personality system, and the organism system. The representation of love and ethics shows that Indonesia’s education world still experiences many shortcomings and problems.Keywords: love, ethics, social action, Talcott Parsons, Guru Aini's novelAbstrak Cinta Kasih dan Etika dalam Perspektif Tindakan Sosial Talcott Parsons dalam Novel Guru Aini Karya Andrea Hirata. Penelitian ini bertujuan mendeskripsikan representasi cinta kasih dan etika dalam perspektif tindakan sosial Talcott Parsons; serta mendeskripsikan representasi cinta kasih dan etika dalam merekonstruksi dunia pendidikan dalam novel Guru Aini karya Andrea Hirata. Metode yang digunakan dalam penelitian ini adalah sosiologi sastra. Sumber data dalam penelitian ini adalah teks novel Guru Aini karya Andrea Hirata. Pengumpulan data dilakukan dengan teknik studi pustaka. Hasil penelitian menemukan 77 tindakan sosial dalam aspek cinta kasih dan etika berdasarkan perspektif tindakan sosial Talcott Parsons. Representasi cinta kasih meliputi cinta kasih kepada orang tua, sesama manusia, dan pekerjaan. Representasi cinta kasih dalam perspektif tindakan sosial Talcott Parsons menunjukkan ada empat tindakan sosial, yaitu sistem kultural, sistem sosial, sistem kepribadian, dan sistem organisme. Representasi etika meliputi etika kepada orang tua, sesama manusia, dan di masyarakat. Representasi etika dalam perspektif tindakan sosial Talcott Parsons menunjukkan ada empat tindakan sosial, yaitu sistem kultural, sistem sosial, sistem kepribadian, dan sistem organisme. Representasi cinta kasih dan etika memperlihatkan bahwa dunia pendidikan di Indonesia masih mengalami banyak kekurangan dan permasalahan.Kata-kata kunci: cinta kasih, etika, tindakan sosial, Talcott Parsons, novel Guru Aini